THEORETICAL FOUNDATIONS OF ARTIFICIAL INTELLIGENCE IN EDUCATION (Uzbekistan Open Conference, 2026)
This paper examines the issues related to artificial intelligence. Artificial intelligence and its technologies have achieved significant success in their development; however, despite this progress, the concept still lacks a clear and universally accepted definition. This can be explained by the fact that artificial intelligence encompasses a wide range of technical and software characteristics and capabilities that can be implemented to achieve various objectives.